Pengaruh Budaya, E-WOM, dan Persepsi Kualitas Produk Terhadap Keputusan Pembelian Tolak Angin - Hidayatullah, Hanif; Amron, Amron; Purwatiningsih, Aris Puji; Oktoriza, Linda Ayu (Jurnal EMT KITA, 2026)
This study aims to analyze the influence of culture, E-WOM, and product quality perception on the purchase decision of Tolak Angin products in Semarang Regency. The use of data in this study came from the distribution of questionnaires through Google Form with purposive sampling techniques and obtained a sample of 112 samples. Data analysis using the SPSS 23.0 device. The use of quantitative methods based on primary data. The statistical analysis technique uses the data quality test method, multiple linear regression, hypothesis test, and F. test which results in (1) culture has a positive and significant effect on the purchase decision of Tolak Angin products. (2) E-WOM has a positive and significant effect on the purchase decision of Tolak Angin products. (3) Product quality perception has a positive and significant effect on the purchase decision of the Wind Repellent product. (4) culture, E-WOM, and product quality perception have a positive and significant effect simultaneously on the purchase decision of Tolak Angin products.